Self-efficacy dan persistensi mahasiswa ketika mengerjakan skripsi ditinjau dari kecemasan akademik - Heru Mugiarso; Ninik Setyowani; Latih Buran Tedra (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
This current research based on phenomenon and problems experienced by finalyear students of FIP Unnes guidance and counseling when doing thesis. The purpose of this study was to investigate the direct effect between self-efficacy and student’s persistence in terms of academic anxiety as a variable mediator. Using bias corrected bootstrap method N = 5000 with 95% confidential interval shows the result that self-efficacy as a predictor on student persistence (β=0,51; p<0,01). While academic anxiety is not proven to have a mediator effect on the relationship between self-efficacy and student persistence. These findings have implications for guidance program of thesis students, especially students majoring in guidance and counseling Unnes FIP.